PEMILIHAN SUPPLIER BERKELANJUTAN PADA INDUSTRI MANUFAKTUR DENGAN MEMPERTIMBANGKAN METODE DAN KRITERIA PEMILIHAN: TINJAUAN PUSTAKA - Afma, Vera Methalina; Hadiguna , Rika Ampuh; Adi , Alexie Herryandie Bronto (JURNAL REKAYASA SISTEM INDUSTRI, 2025)
Supplier selection plays a pivotal role in the operational efficiency and cost management of manufacturing industries. Appropriate supplier choice directly affects the production costs and overall competitiveness of a company. This study aims to explore the supplier selection process within manufacturing firms through the application of Multi-Criteria Decision Making (MCDM) methods. A systematic literature review was conducted using scientific articles indexed in Scopus, analyzed with the Bibliometrix package in R Language. The findings highlight various MCDM approaches utilized in supplier evaluation and selection, along with the key criteria considered in decision-making processes. This research contributes to a deeper understanding of methodological trends and practical considerations in supplier selection, offering insights for both academic and industrial applications. Keywords: supplier selection, manufacturing, MCDM, literatur review